Optimalisasi Tata Kelola Administrasi Surat-Menyurat melalui Pengembangan Sistem E-Arsip di Kecamatan Tarub - Isnaen Soleh Ibrohim; Aang Alim Murtopo; R. Bangkit Indarmawan; Syefudin Syefudin (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The rapid development of information technology has encouraged government institutions to adopt digital transformation to improve administrative efficiency and service quality. The Tarub District Office manages incoming and outgoing correspondence, which previously relied on manual recording and physical archives, making document retrieval and archive management inefficient. This study aimed to develop a web-based e-archiving information system to improve the management of correspondence archives. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model, including requirements analysis, system design, implementation, and testing. The application was built using PHP with the CodeIgniter framework, MySQL as the database, and Bootstrap for the user interface. The resulting system provides features for managing user data, employee data, archive codes, external agencies, incoming and outgoing correspondence, activity agendas, dispositions, and report generation. Functional testing covered form validation, document retrieval, file uploading, user access rights, and report generation, with all features operating successfully according to system requirements. The implementation of the e-archiving system improves the efficiency, accuracy, and organization of correspondence management at the Tarub District Office, thereby supporting higher-quality public administration services.